What Makes Discrimination Wrong? - De Font-Reaulx, P (Oxford Uehiro Centre for Practical Ethics, 2017)
Most of us intuitively take discrimination based on gender or ethnicity to be impermissible because we have a right to be treated on the basis of merit and capacity rather than e.g. ethnicity or gender. I call this suggestion the Impermissibility Account. I argue that, despite how the Impermissibility Account seems intuitive to most of us with a humanist outlook, it is indefensible. I show that well-informed discrimination can sometimes be permissible, and even morally required, meaning we cannot have a strict right not to be discriminated against. I then propose an alternative and more plausible account which I call the Fairness and Externalities Account, arguing that acts of discrimination are wrong partly because they are unfair and partly because they create harmful externalities which—analogously to pollution—there is a collective responsibility to minimize. Both of these factors are however defeasible, meaning that if the Fairness and Externalities Account is correct, then discrimination is sometimes permissible. These results are counterintuitive, and suggest that the ethics of discrimination requires further attention.